COMMUNITY PERCEPTIONS AND ADAPTATION STRATEGIES TO THE IMPACTS OF CLIMATE CHANGE IN THE LANDSCAPE OF PERANGAI VILLAGE, LAHAT REGENCY - Freda Zelika; Heripan Heripan; Delfy Lensari, S.Hut, M.Si (Universitas Muhammadiyah Palembang, 2025)
Climate change is a global phenomenon that significantly affects the agricultural sector, particularly in rural areas that depend heavily on climate conditions. This study aims to analyze community perceptions, the impacts of climate change, and adaptation strategies adopted by the people of Perangai Village. The method used was a survey combined with interviews involving local farmers. The results show that the majority of the community (72%) agrees that climate change has occurred, indicated by unpredictable weather patterns, environmental changes, and declining agricultural yields that affect livelihoods. The impacts include reduced productivity of major crops such as coffee, rubber, rice, and vegetables due to changes in temperature, rainfall patterns, and increased pest and disease attacks.Adaptation strategies undertaken by the community include the use of vinegar to solidify rubber latex, land-use conversion, planting shade trees for coffee, using organic fertilizers, adjusting planting schedules, improving irrigation systems, and implementing intercropping systems for vegetables. However, these adaptations are still relatively simple and based on local experience. This study highlights the importance of increasing community knowledge and government support through education and outreach programs to strengthen adaptive capacity toward climate change.